2017
DOI: 10.1002/jmv.24770
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of hepatitis B and C virus infections among blood donors in Ethiopia

Abstract: This study was conducted to investigate the prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) infections among blood donors in different regions in Ethiopia. A total of 56 885 sera were tested for HBsAg and anti-HCV antibodies. Of these, 3.9% were found HBsAg-positive, 0.52% anti-HCV-positive, and 0.054% dual positive. HBV prevalence was relatively higher in Adama (5.91%) than Gondar (4.05%), Jimma (3.87%), Addis Ababa (3.75%), and Tigray (3.7%); and in males (4.64%) than females (2.1%). Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The low HIV prevalence in our CHB cohort, therefore, is mirroring the HIV prevalence in the general population in Ethiopia, which is estimated to be 1.2% [12]. Similarly, the low proportion with HBV/HCV co-infection in our study is probably a reflection of the overall low prevalence of HCV in Ethiopia [32]. The presence of anti-HDV antibodies in our study was also relatively low, which is in line with a previous study from East Africa; however, available data from the region is scarce [33].…”
Section: Discussionmentioning
confidence: 56%
“…The low HIV prevalence in our CHB cohort, therefore, is mirroring the HIV prevalence in the general population in Ethiopia, which is estimated to be 1.2% [12]. Similarly, the low proportion with HBV/HCV co-infection in our study is probably a reflection of the overall low prevalence of HCV in Ethiopia [32]. The presence of anti-HDV antibodies in our study was also relatively low, which is in line with a previous study from East Africa; however, available data from the region is scarce [33].…”
Section: Discussionmentioning
confidence: 56%
“…The largest HCV survey of blood donors conducted on 56,885 donors in five regional blood banks found HCV prevalence of 0.5%. 26 In other studies elsewhere in Ethiopia, HCV prevalence in blood donors ranges from 0.2% to 1.3% 2,5,55-57 A 6-year retrospective study of 11,382 blood donors from 2008 to 2015 found a significant increase in HCV prevalence (P-value for linear trend = 0.001). 33 Universal screening and treatment for HCV infection of all blood donors will ensure access to HCV treatment, which in turn accentuates micro-elimination.…”
Section: Resultsmentioning
confidence: 90%
“…One of the opportunities that positively support future HCV elimination initiatives is the low prevalence of the infection in the population, although data came from sparse reports of subpopulationbased studies. 2,4,10,26 The implication of having low burden in the country is that the limited healthcare resources could be directed toward screening and treatment of HCV infection in most at-risk populations. An expert review identified that injecting drug use is low in Ethiopia.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 56,885 sera were collected, of which 294 were tested anti-HCV antibody positive in Ethiopia [17]. Of these, 98 sera were stored at −80°C until use and shipped to the Netherlands for further molecular study.…”
Section: Methodsmentioning
confidence: 99%